Organizing Wal-Mart: The Canadian Campaign - Adams, Roy J (Just Labour, 2005)
The central focus of this article is the effort by Canadian unions to organize Wal-Mart. Organizing the world's largest corporation is considered to be critical because the company's business "template" calls for wages and benefits considerably inferior to those of unionized workers. To date, although a few bargaining units have been certified, Wal-Mart has managed to thwart all attempts to negotiate collective agreements. However, because the United Food and Commercial Workers have certified units in a few provinces with first contract arbitration, the achievement, eventually, of a collective agreement appears to be likely.